2017
DOI: 10.7150/jca.18026
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of miRNAs in exosomes derived from serum of colon cancer patients

Abstract: Objective: To isolate exosomes from the serum of colon cancer patients and identify RNAs in the small vesicles.Methods: ExoQuick-TC™ Exosome Precipitation Solution was used for exosome isolation and the shapes of exosomes were observed under a transmission electron microscope. Mass spectrometry was used to identify the classification of miRNAs encapsulated in exosomes, and the expression levels of miRNA-21,-133a, and -181b in exosomes were detected by RT-PCR.Results: Exosomes isolated from serum of colon cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…Recently, exosomes, and in particular neuronally derived exosomes, have been studied as potential biomarkers of NDs [ 99 101 ]. The promise of exosomes as biomarkers of pathology is due largely to their protein content and membrane composition because there is a high degree of variability in miRNA distribution across exosome populations, and contradictory data exist on the fraction of miRNAs circulating in exosomes as compared with other forms of cell-free miRNAs in the bloodstream [ 47 , 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, exosomes, and in particular neuronally derived exosomes, have been studied as potential biomarkers of NDs [ 99 101 ]. The promise of exosomes as biomarkers of pathology is due largely to their protein content and membrane composition because there is a high degree of variability in miRNA distribution across exosome populations, and contradictory data exist on the fraction of miRNAs circulating in exosomes as compared with other forms of cell-free miRNAs in the bloodstream [ 47 , 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…The engineered CV‐1 cell membrane was derived with combined mechanical disruption and differential centrifugation . Then, a previously reported MB was synthesized to detect a model exosomal miRNA, miR‐21, which is a universal biomarker of many cancers including breast, lung, colon, and brain cancers . The MBs were mixed with the cell membrane and coextruded through porous polycarbonate membranes to generate the Vir‐FVs.…”
Section: Methodsmentioning
confidence: 99%
“…64 Furthermore, it was demonstrated that miR-21 is significantly overexpressed (five folds) in exosomes derived from patients with colon cancer, particularly in patients at the first diagnosis or before any treatments. 113 Generally, a unique miRNA like miR-21 is not an exact diagnostic marker in CRC; it requires to be accompanied with other miRNAs for improved specificity. 60 Another study in this area showed that exosomal miR-193a may be used as a biomarker for predicting the progression of colon cancer.…”
Section: Of Crcmentioning
confidence: 99%